TRADITIONAL AND PROGRESSIVE PEDAGOGICAL APPROACHES IN PRIMARY EDUCATION - Ziyomuxammad Nematov (Web of Journals Publishing, 2024)
The article discusses the importance of effective pedagogical approach of teaching in primary education. Two different approaches are analyzed and presented in the article. Also, the key differences between them as well as their advantages and disadvantages are identifies throughout the article with valid examples and evidences.
Keywords: Primary education, teaching approaches, pedagogical methods, primary school children, progressive approach to teaching, traditional approach to teaching, importance of effective teaching, teaching.